2010
DOI: 10.1093/toxsci/kfq010
|View full text |Cite
|
Sign up to set email alerts
|

SO2 Inhalation Contributes to the Development and Progression of Ischemic Stroke in the Brain

Abstract: Epidemiological literatures show an association between air pollution and ischemic stroke, and effective pollutants may include SO(2), NO(x), O(3), CO, and particulates. However, existing experimental studies lack evidence as to the presence of effects for SO(2), which has been the focus in developing countries with increasing use of coal as the main resource. In the present study, we treated Wistar rats with SO(2) at various concentrations and determined endothelin-1 (ET-1), inducible nitric oxide synthase (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
106
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 282 publications
(109 citation statements)
references
References 45 publications
1
106
0
2
Order By: Relevance
“…On the other hand, sulfur dioxide (SO 2 ) is one of the most widely distributed air pollutants and is well known to have significant impacts upon human health [4]. Studies have shown that frequent exposure to SO 2 not only induces many respiratory responses [5], but is also linked to lung and brain cancer, cardiovascular disease, and neurological disorders [6]. Since SO 2 can be easily hydrated to sulfurous acid once inhaled and subsequently forms equilibrium of its derivatives bisulfite and sulfite as its main form in aqueous media, the toxicity of SO 2 is considered mainly by these two anions [7].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, sulfur dioxide (SO 2 ) is one of the most widely distributed air pollutants and is well known to have significant impacts upon human health [4]. Studies have shown that frequent exposure to SO 2 not only induces many respiratory responses [5], but is also linked to lung and brain cancer, cardiovascular disease, and neurological disorders [6]. Since SO 2 can be easily hydrated to sulfurous acid once inhaled and subsequently forms equilibrium of its derivatives bisulfite and sulfite as its main form in aqueous media, the toxicity of SO 2 is considered mainly by these two anions [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the study, rats (n = 6/group) were exposed for 6 h/d for 7 d to fresh air, 5, 10 or 20 mg/m 3 NO 2 using protocol of dynamic inhalation based on our previous studies [25,26]. During exposure period, the four groups of rats were placed in 1 m 3 exposure chambers simultaneously.…”
Section: Animal Exposure and Treatment Protocolsmentioning
confidence: 99%
“…Inhaling SO2 is associated with increased respiratory symptoms and responses, and recent studies also imply that SO2 exposure is linked with many neurological disorders, such as stroke and brain cancer (Kampa and Castanas, 2008;Sang et al, 2010). SO2 derivatives were shown to cause apoptotic neuronal death through regulating several apoptosis-related genes, such as p53, bax, bcl-2 and c-jun .…”
Section: Introductionmentioning
confidence: 99%